Tactile field and the dual nature of touch: Poster - Skrzypulec, Błażej (My University, 2021)
I investigate whether it is justified to postulate tactile field analogous in its properties to visual field. I argue that the answer is both ‘yes’ and ‘no’ due to the dual nature of touch: touch is both an interoceptive modality which presents states of one’s body and an exteroceptive modality which presents external entities. More specifically, the interoceptive tactile space, in which tactile bodily sensations are experienced to be localized, has a character of a spatial field. On the other hand, the exteroceptive tactile space, in which external, tactile objects are experienced to be localized does not have field-status.
Keywords: tactile perception; interoception; exteroception; spatial perception; Research Subject Categories::NATURAL SCIENCES